Surface-Engineered Nanostructure-Based Efficient Nonpolar GaN Ultraviolet Photodetectors - Mishra, Monu; Gundimeda, Abhiram; Krishna, Shibin; Aggarwal, Neha; Goswami, Lalit; Gahtori, Bhasker; Bhattacharyya, Biplab; Husale, Sudhir; Gupta, Govind (ACS omega, 2018)
Surface-engineered nanostructured nonpolar (112̅0) gallium nitride (GaN)-based high-performance ultraviolet (UV) photodetectors (PDs) have been fabricated. The surface morphology of a nonpolar GaN film was modified from pyramidal shape to flat and trigonal nanorods displaying facets along different crystallographic planes. We report the ease of enhancing the photocurrent (5.5-fold) and responsivity (6-fold) of the PDs using a simple and convenient wet chemical-etching-induced surface engineering. The fabricated metal–semiconductor–metal structure-based surface-engineered UV PD exhibited a significant increment in detectivity, that is, from 0.43 to 2.83 (×108) Jones, and showed a very low noise-equivalent power (∼10–10 W Hz–1/2). The reliability of the nanostructured PD was ensured via fast switching with a response and decay time of 332 and 995 ms, which were more than five times faster with respect to the unetched pyramidal structure-based UV PD. The improvement in device performance was attributed to increased light absorption, efficient transport of photogenerated carriers, and enhancement in conduction cross section via elimination of recombination/trap centers related to defect states. Thus, the proposed method could be a promising approach to enhance the performance of GaN-based PD technology.